2012
DOI: 10.1097/01.ehx.0000418063.67260.66
|View full text |Cite
|
Sign up to set email alerts
|

Expression of estrogen receptors-α in testicular biopsies from nonobstructive azoospermic patients

Abstract: BackgroundAlthough the importance of estrogen in male reproduction is indisputable, little attention has been paid to the role of the estrogen receptor in male infertility. Aim of the workThis study aimed to evaluate the immunohistochemical localization of estrogen receptor-α (ER-α) in testicular biopsies from nonobstructive azoospermic (NOA) patients compared with the control. Patients and methodsThis study was carried out on 50 infertile men diagnosed with (NOA): 12 were hypospermatogenesis (HP), 22 were mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…In the present study, patients with SCO (GIIA) revealed aggregations of Leydig cells with no or ill‐defined intercellular boundaries and significant higher FSH levels compared to GI. Previous studies reported apparent hyperplasia of Leydig cells within the interstitial tissue in patients with SCO (Farghaly, Mohamed, & Mostafa, ). Our results revealed that the mean count of CD68‐immunoreactive interstitial macrophages showed nonsignificant decrease in GIIA compared to GI, while it showed a nonsignificant increase compared to other groups of NOA (GIIB or GIIC).…”
Section: Discussionmentioning
confidence: 78%
“…In the present study, patients with SCO (GIIA) revealed aggregations of Leydig cells with no or ill‐defined intercellular boundaries and significant higher FSH levels compared to GI. Previous studies reported apparent hyperplasia of Leydig cells within the interstitial tissue in patients with SCO (Farghaly, Mohamed, & Mostafa, ). Our results revealed that the mean count of CD68‐immunoreactive interstitial macrophages showed nonsignificant decrease in GIIA compared to GI, while it showed a nonsignificant increase compared to other groups of NOA (GIIB or GIIC).…”
Section: Discussionmentioning
confidence: 78%